Development of a membrane-less microfluidic thermally regenerative ammonia battery. (15th June 2021) - Vicari, Fabrizio; Galia, Alessandro; Scialdone, Onofrio
Abstract: Thermally regenerative ammonia battery is a promising approach to make use of waste heat and generate electrical energy. However, according to literature, the price of the energy obtained by this device is much higher than alternative renewable technologies (such as wind, solar, geothermal, etc.). To make the process more viable for applicative purposes, it would be necessary to reduce dramatically the cost of the membrane or to avoid it. Hence, the aim of the present work is to increase the economic figures of thermally regenerative ammonia battery avoiding the use of membranes. It was concluded that this result can be obtained by developing the process in a microfluidic flow cell with laminar flow conditions. In particular, it has been demonstrated for the first time that it is possible to obtain quite high power densities in the absence of a membrane in a micro cell. By operating the process at proper flow rates and inter-electrode distances, the membrane-less microfluidic thermally regenerative ammonia battery allowed to achieve even higher power densities than conventional TRAB operated under batch mode and similar operating conditions. In addition, it was shown that the process can be improved using copper deposited on carbon electrodes and moderate temperatures. In fact, at 50 °C a power density of 73.4 W m −2 was obtained. Highlights: A Thermally Regenerative Ammonia Battery was operated for the first time in the absence of membrane. Power density obtained by mmTRAB are higher than that obtained in a conventional divided cell. Flow rate and inter-electrode distance affect greatly the performances of the process. Higher temperatures improve power density production.